Why it’s time to say goodbye to stavudine ... everywhere - Isabelle Andrieux-Meyer; Polly Clayden; Simon Collins; Nathan Geffen; Eric Goemaere; Mark Harrington; Sharonann Lynch; Tido von Schoen-Angerer; Tracy Swan (Southern African Journal of HIV Medicine, 2012)
The previous issue of the SAJHIV (December 2011) carried an Opinion piece by Innes, Cotton and Venter regarding the potential value of low-dose of stavudine (20 mg twice a day). They suggested that reduced dosing of stavudine may lead to levels of viral suppression comparable with those achieved with stavudine 30 mg bd but with a lower risk of toxicity and side-effects, and at a fraction of the cost of tenofovir. The Opinion was related to a larger proposal, led by Venter, to conduct a head-to-head trial comparing low-dose stavudine with tenofovir (both in a regimen including lamivudine and efavirenz) on viral suppression and other treatment outcomes over 24 months. There has been considerable debate regarding the advantages and disadvantages of low-dose stavudine, and in turn the value of any such trial. Here the debate continues with a commentary by Isabelle Andrieux-Meyer et al. and a rebuttal by Venter and colleagues.